Are we there yet? Time for checks and balances on new institutionalism - Murat Iyigun (Institute for the Study of Labor (IZA), 2012)
New institutionalism has had considerable success during the last decade in shepherding the debate on sustained economic development. If the sociopolitical, legal and economic transformations in the Anglo-Saxon world in the last three decades prove anything, however, it is that the late Mancur Olson deserves some long overdue credit. For the relevant question now is why have some constitutional democracies deteriorated to the point of chronic dysfunction with their checks and balances failing. New institutionalists then ought to come to terms with the fact that, in the interest of credible empirical identification, they too narrowly defined what Northian institutions entail. As a matter of fact, political, legal and economic institutions are highly malleable even in advanced economies, while sustained economic growth could well be deep rooted in individual beliefs, social norms and informal cultural organizations.
Keywords: O11; O57; N10; 330; institutions; economic growth; development; Institutionalismus; Wirtschaftswachstum; Entwicklung; Institutioneller Wandel; Welt